If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(z + -5) = -2z Reorder the terms: -2(-5 + z) = -2z (-5 * -2 + z * -2) = -2z (10 + -2z) = -2z Add '2z' to each side of the equation. 10 + -2z + 2z = -2z + 2z Combine like terms: -2z + 2z = 0 10 + 0 = -2z + 2z 10 = -2z + 2z Combine like terms: -2z + 2z = 0 10 = 0 Solving 10 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 9+3x=33+x | | 6x+32=16x-58 | | x^3-3x^2=-3x+1 | | 11x-37=5x+5 | | x^3-3x^2+3x-1=0 | | 6x+27=8x+11 | | 8x+9=3x+39 | | X^3+3x-40=0 | | (9+(4-3)-17)= | | 5x-6=4x-2 | | 1000k+2500d=5150 | | 521x+214p=800 | | 5x+67=11x+13 | | -6x+9+4x=-3 | | 9X+7Y=0 | | 2x+3(x-9)-2(x+3)=0 | | -2(-3-4x)=-10 | | 7x-2(x+6)=3 | | 3n+3(1-n)-n=-6 | | 6x-(x+7)=13-5 | | 5(2r-2)=9r | | 4a-(a+6)=12-36 | | 5(2-2)=9 | | 4x-2(x-5)=-2 | | 3(b+2)+2(b-3)=-5 | | 5(2a-2)+4=4 | | 3x-2(x+4)=8 | | 3(y-4)=15 | | 2(x-3)-x=-1 | | 12=3x-x+4x | | 6x+2x=-64 | | z-4-4z=-1 |